Biomedical payloads: A maturing application for CubeSats. (February 2022) - Robson, Daniel J.; Cappelletti, Chantal
Abstract: This paper outlines some of the challenges and opportunities facing the space biomedical community and how CubeSats may (and indeed already are) supporting this research area. A review of current space and microgravity platforms capable of supporting biomedical research is presented alongside a summary of the vital research that this enables. This paper presents biomedical CubeSat enabling technology alongside the critical technology gaps is given, alongside analysis of relevant logistical and bureaucratic factors in the space sector. An overview of the general design requirements for biomedical CubeSat missions is presented to help support potential new developers, alongside a small review of some of the technology gaps and innovations that are present and of importance to the sector's maturity. Finally, we demonstrate that CubeSats do have the potential to become a mature and high-fidelity niche in the NewSpace infrastructure, that could support professionally-credible space biomedical research, complementing traditional platforms such as crewed vehicles, autonomous biosatellites and free-flyers. Biomedical CubeSats have been validated through a well-documented programme of NASA missions, as well as successful flights from at least one commercial company to date, and now these trail-blazers are being followed by a new "mini-space race" among Universities and other groups. This report aims to review the status and estimate in which scenarios a biomedical CubeSat mission would provide cost-effective, worthwhile science return, versus (arguably) the most common current route to space for biomedical payloads – the ISS. It aims to act as a primer and provide information for potential mission planners or scientists that are newer to the space sector and want a ground-up analysis of some of the routes to space. Importantly, this paper compares the biomedical CubeSat versus a payload hosted on a platform like the ISS, and not any of the other high-profile, and potentially very popular, current or developing platforms that are only briefly referenced. Highlights: A primer for groups looking to embark upon biomedical space research using CubeSats. A review of current platforms capable of supporting space biomedical research. A comparison of biomedical CubeSats to the current main "route-to-space" (the ISS). A review of biomedical CubeSat enabling technology and critical technology gaps. Discussion of relevant logistical and bureaucratic factors related to biomedical CubeSats. Overview and guidance for future mission developers and biomedical scientists.